Necrotizing fasciitis: Epidemiology and clinical predictors for amputation - Patcharin Khamnuan (2018)
© 2015 Khamnuan et al. Background: Necrotizing fasciitis, a relatively uncommon infection involving the skin, subcutaneous tissue, and fascia, is a rapidly progressive soft tissue infection and a medical and surgical urgency. Delayed debridement, with subsequent huge soft tissue loss is associated with loss of limb and infection and is the most common cause of mortality. The purpose of this work is to describe the epidemiology of necrotizing fasciitis and to identify the clinical characteristics that may be used to predict amputation in routine clinical practice. Methods: Retrospective cohort study data were collected from three general hospitals located in the Chiang Rai, Kamphaeng Phet, and Phayao provinces in northern Thailand. Epidemiologic data for all patients with a surgically confirmed diagnosis of necrotizing fasciitis between 2009 and 2012 were collected. Medical records and reviews were retrieved from inpatient records, laboratory reports, and registers. Clinical predictors for amputation were analyzed by multivariable risk regression. Results: A total of 1,507 patients with a diagnosis of necrotizing fasciitis were classified as being with amputation (n=127, 8.4%) and without amputation (n=1,380, 91.6%). The most common causative Gram-positive and Gram-negative pathogens were Streptococcus pyogenes (33.3% in the amputation group and 40.8% in the non-amputation group) and Escherichia coli (25% in the amputation group and 17.1% in the non-amputation group). Predictive factors for amputation included gangrene (risk ratio [RR] 4.77, 95% confidence interval [CI] 2.70–8.44), diabetes mellitus (RR 3.08, 95% CI 1.98–4.78), skin necrosis (RR 2.83, 95% CI 2.52–3.18), soft tissue swelling (RR 1.76, 95% CI 1.24–2.49), and serum creatinine values ≥1.6 mg/dL on admission (RR 1.71, 95% CI 1.38–2.12). All data were analyzed using the multivariable risk regression generalized linear model. Conclusion: The most causative pathogens were S. pyogenes and E. coli. Clinical predictors for amputation in patients with necrotizing fasciitis included having diabetes mellitus, soft tissue swelling, skin necrosis, gangrene, and serum creatinine values ≥1.6 mg/dL on admission. Thus, patients with any of these predictors should be monitored closely for progression and receive early aggressive treatment to avoid limb loss.